APICULTURE AS AN INCOME ALLEVIATION IN THREE VILLAGES OF SOUTH WEST KHASI HILLS, MEGHALAYA - WANSWETT, I.; MARNGAR, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Beekeeping acts as a subsidiary occupation in rural areas which farmers and entrepreneurs take up as to generate additional income. The study focuses on how much that income generated through beekeeping over the years. If the income of the household from beekeeping played a role in generating an extra income to the households in these villages. Most of the studies focus on the problems of beekeeping rather the role of income from beekeeping in reducing poverty in rural areas. The collection of honey for household consumption has been done for generations but the exploitation for commercial purposes has gain momentum in the present scenario. The aim of the study is to examine that beekeeping can be considered as one of the solutions for poor households in rural areas to enhance their household income. The objectives of the study are to know about the households in the villages, the role that beekeeping played in breaching the gap between farm and non-farm activities and increasing the households’ income over the years. The research design was based on the three villages with a purposive sampling and based on a random sampling in choosing the samples of beekeepers. Results obtained shows that with globalisation and the spread of social media, the market for export of honey even from remote areas has increase and this has made beekeeping as a subsidiary occupation. Apiculture in Meghalaya can be considered as a subsidiary occupation which can help in poverty reduction and as a supplement to the household income in rural areas. Even though beekeeping is a significant subsidiary occupation for households in rural areas for increasing income it still has a long way to go to make it more viable. The pricing of the honey sold should be determined so that it does not take away the profit from the primary producers, good advertisement is needed and there is a need for community linkage to further add to the growth of commercialisation of honey and its products.